IMPLEMENTASI DATATABLES SERVER-SIDE UNTUK MEMPERCEPAT LOAD HALAMAN PADA APLIKASI E-COMMERCE - Ardian Dwi Praba; Maryanah Safitri; Faridi Faridi (University of Muhammadiyah Tangerang, 2021)
Large amounts of data are a new challenge in Industry 4.0 at this time, where the data must be accessed and processed quickly by computers. Large data causes the data presentation process to be very long because all data must be processed in one go. So that we need a special technique so that the presentation of information runs quickly even though the data that must be subject to the number is very large. In general, the website requsets the server, if the server data system exists, the data will be sent by the server to the client according to the number of existing data processes. The more data sent by the server, the longer it will take the client to display existing data. In this research, we will try to use server-side processing datatables where all processes will be carried out on the server side and data is sent periodically to the client according to the input request or keyword. The conclusion of this research is that the data speed using server side processing techniques is 7,9% of client side processing.